Respuesta :
Answer:
-44
Step-by-step explanation:
We have the expression
[tex]-2|6x - y|[/tex]
We need to find the value of the expression when x = -3 and y = 4
Then we must replace the variable with the number -3 and the variable y with the number 4
This is:
[tex]-2|6(-3) - (4)|[/tex]
[tex]-2|-18 - 4|[/tex]
[tex]-2|-22|[/tex]
Remember that the absolute value always results in a positive number.
So
[tex]-2|-22| = -2(22)=-44[/tex]
the answer is -44
Answer:
The correct answer is -44
Step-by-step explanation:
Points to remember
|x| = x
|-x| = x
To find the value of –2|6x – y|
We have –2|6x – y| When x = -3 and y = 4
Substitute the value of x and y
–2|6x – y| = –2|(6 * -3) – 4|
= -2|-18 - 4|
= -2|-22|
= -2 * 22
= -44
Therefore the value of –2|6x – y| when x = -3 and y = 4
–2|6x – y|